Metabolomics profiling reveals different patterns in an animal model of asphyxial and dysrhythmic cardiac arrest. Issue 1 (December 2017) - Varvarousis, Dimitrios; Xanthos, Theodoros; Ferino, Giulio; Noto, Antonio; Iacovidou, Nicoletta; Mura, Massimo; Scano, Paola; Chalkias, Athanasios; Papalois, Apostolos; De-Giorgio, Fabio; Baldi, Alfonso; Mura, Paolo; et al.
Abstract Cardiac arrest (CA) is not a uniform condition and its pathophysiology strongly depends on its cause. In this work we have used a metabolomics approach to study the dynamic metabolic changes occurring in the plasma samples of a swine model following two different causes of CA, namely asphyxia (ACA) and ventricular fibrillation (VFCA). Plasma samples were collected at baseline and every minute during the experimental phases. In order to identify the metabolomics profiles characterizing the two pathological entities, all samples were analysed by1 H NMR spectroscopy and LC-MS/MS spectrometry.The metabolomics fingerprints of ACA and VFCA significantly differed during the peri-arrest period and the resuscitation phase. Major alterations were observed in plasma concentrations of metabolites related to tricarboxylic acid (TCA) cycle, urea cycle, and anaplerotic replenishing of TCA. ACA animals showed significant metabolic disturbances during the asphyxial and CA phases, while for VFCA animals this phenomenon resulted shifted at the resuscitation phase. Interestingly, starting from the asphyxial phase, the ACA animals were stratified in two groups based on their metabolomics profiles that resulted to be correlated with the clinical outcome. Succinate overproduction was observed in the animals with the worse outcome, suggesting a potential prognostic role for this metabolite.